PENINGKATAN PARTISIPASI SISWA DENGAN MODEL INKUIRI BERBASIS CTL (CONTEXTUAL TEACHING AND LEARNING) PADA PEMBELAJARAN KEWARGANEGARAAN - Buchory Muh Sukemi; Sukemi, Samid Sukemi, Samid; Rusdijati Rusdijati (LPMPP Universitas Negeri Yogyakarta, 2007)
This article is about a classroom action research concerned withthe research problemof whether learners' participation in Class XIIPA 2 at State Senior High School 1, Jetis, Bantul, Yogyakarta, inthe civics education class could be improved with the inquirylearning model based on the conceptof Contextual Teaching andLearning (CTL). The research was intended to improve the learners'participation and to describe their learning achievement in the civicseducation class employing the inquiry learning model based onCTL.The classroom action research was carried out through aprocedure consistingof the following steps: (l) action planning toprepare for the research and for conventional learning performance;(2) action implementation in two cycles; (3) observation,in whichany phenomenon taking place during the implementationof thestudy was observed and recorded; and (4) action evaluation andreflection, in which the weaknesses, insufficiencies, difficulties, andefficacies in improving students' participation were identified. Thesubjectsof this research were students of Class XI IPA 2 at StateSenior High School1, Jetis, Bantul, Yogyakarta.The research results revealed the following findings: (1) with theinquiry learning model based on CTL, students' participation in thecivics education class couldbe improved from the activeparticipationof 15 students (39%) in cycle 1 to that of 33 students(87%) in cycle 2 and (2) students' learning achievement in the civics education class could be improved from the positiveachievementof 17 students (45 %) in cycle 1 to that of 37 students(970/0) in cycle 2